Effect of coaching behaviors on job satisfaction and organizational commitment: The case of comprehensive community sport clubs in Japan - Takamatsu, S.; Yamaguchi, Y. (International Journal of Sports Science & Coaching, 2018)
Coaches are widely regarded as playing an important role in the development of comprehensive community sport clubs, in terms of meeting the needs of club members and club staff. However, few studies have explored the coaching activities of comprehensive community sport clubs in Japan. This study, therefore, aimed to examine the effect of coaching behaviors in comprehensive community sport clubs on job satisfaction and organizational commitment. One hundred seventy-seven coaches completed questionnaires assessing coaching behaviors in comprehensive community sport clubs, job satisfaction, and organizational commitment. The scale measuring coaching behaviors in comprehensive community sport clubs was comprised of seven factors: (1) manner education, (2) cooperative approach, (3) field management, (4) coaching skills, (5) communication with people outside the club, (6) communication with people inside the club, and (7) safety management. Path analysis with structural equation modeling revealed cooperative approach and field management influenced job satisfaction. The study additionally indicated job satisfaction positively impacted organizational commitment. Furthermore, communication with people inside the club directly influenced on organizational commitment. Thus, it was concluded that creating a sporting environment in which coaches can behave autonomously, as well as providing a space where coaches can communicate with many people, are necessary preconditions to increase job satisfaction and organizational commitment of coaches in comprehensive community sport clubs.